2014
DOI: 10.9790/1959-03311621
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Surgical Site Infections (SSIs) among Patients Undergoing Major Surgery at General Hospital Funtua, Katsina State, Nigeria

Abstract: Surgical site infection is one of the most common preventable complications following major

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…[ 14 ] Most existing local studies on SSI lack reports on anaerobic components of wound infection. [ 5 6 7 8 19 ] Anaerobic organisms isolated in this study were from deep and organ SSI involving the gastrointestinal tract. This agrees with other reports that anaerobes are the predominant organisms in the gastrointestinal tract.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…[ 14 ] Most existing local studies on SSI lack reports on anaerobic components of wound infection. [ 5 6 7 8 19 ] Anaerobic organisms isolated in this study were from deep and organ SSI involving the gastrointestinal tract. This agrees with other reports that anaerobes are the predominant organisms in the gastrointestinal tract.…”
Section: Discussionmentioning
confidence: 99%
“…[ 4 ] There is an overwhelming burden of SSI in developing countries because of poverty, poor infection control, high antibiotic resistance rates, and inadequate laboratory services. For instance, studies from various parts of Nigeria revealed incidence rates of SSI between 12.5% and 17.4% for SSIs[ 5 6 7 8 ]…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations